Fire Protection System Evaluation in the Oncology Center Building of Hospital in Surabaya - Debora Dzahabiyyah; Dani Nasirul Haqi; Suhariono Suhariono (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: The Oncology Center Building is the part of Hospital X Surabaya that focuses on developing cancer services. As a type A hospital, Hospital X is required to have a preparedness program in the facilities and infrastructure for fire protection and prevention. The purpose of this study was to evaluate the fire protection facilities and infrastructure in the Oncology Center Building of Hospital X Surabaya. Methods: This study was an observational study using a cross-sectional approach. The data analysis method used was descriptive. The primary data collection was carried out through interviews with the Hospital Occupational Safety and Health committee of Hospital X and the secondary data was in the form of profiles on Hospital X, as well as its policies, programs, guidelines, and SOPs related to fire prevention in Hospital X. Results: Active fire protection facilities and infrastructure in the form of fire detectors and fire alarms are in accordance with SNI 03-3985-2000. Meanwhile, other active fire protection facilities and infrastructure, such as fire extinguishers, hydrants, and sprinklers, are still not in accordance with the applicable policies because there are several elements that have not been fulfilled. The passive fire protection facilities and infrastructure are still not in accordance with existing policies because there are no walls, windows, and fireproof glass in the Oncology Center Building. Conclusion: The active and passive fire protection facilities and infrastructure in the Oncology Building, Hospital X still do not comply with the applicable policy because there are several elements of each fire protection facility and infrastructure that do not meet the specified standards.